Squamous Cell Carcinoma in Combination with a Symbrachydactyly: Initial Management and Long-Term Followup - Tomas Sanchez; Daniel Walder; Philipp Esenwein (Case Reports in Orthopedics)
A 68-year-old female patient presented with a rapidly growing, exulcerating tumor of the left hand in the area of a congenital symbrachydactyly at the digiti II and III. A biopsy of the tumor showed a squamous cell carcinoma. Further workup showed two suspicious axillar enhancements with no evidence of bony infiltration and no further metastasis. An amputation of the second and third ray of the left hand at the metacarpal level and additionally an axillar revision and lymph node dissection were performed and confirmed the suspicion of a squamous cell carcinoma, fortunately without affection of any lymph nodes. After 9 years the patient showed an excellent function of the left hand. Symbrachydactyly malformations and squamous cell carcinoma of the hand are both rare conditions. We could not find a reference that shows a common genetic condition to both and so far this is the first description of a squamous cell carcinoma in the region of a symbrachydactyly. It remains unclear whether our case is a coincidence of two rare independent diseases or there is a pathogenetic link between the malformation and the tumor on a genetic level.